Folic acid supplements during pregnancy and risk of miscarriage. - Gindler J; Li Z; Berry RJ; Zheng J; Correa A; Sun X; Wong L; Cheng L; Erickson JD; Wang Y; Tong Q; Gindler, J; et al. (Lancet, 2001)
Background: Although taking supplements that contain 400 microg of folic acid before and during early pregnancy reduces a woman's risk for having a baby with a neural-tube defect (NTD), the effects of such supplements on other pregnancy outcomes remain unclear. We examined whether the use of such supplements affects the occurrence of miscarriage.Methods: Participants were women in China who had taken part in a recent folic acid campaign to prevent NTDs and who had registered in this campaign before they became pregnant for the first time. We examined the risk for miscarriage among women who had confirmed pregnancies and who had or had not taken pills containing only 400 microg of folic acid before and during early pregnancy.Results: The overall rate of miscarriage was 9.1% (2155/23806). The rates of miscarriage among women who had and had not taken folic acid pills before and during the first trimester were 9.0% and 9.3%, respectively (risk ratio 0.97 [95% CI 0.84-1.12]). The distributions of gestational age at pregnancy diagnosis and at miscarriage were similar for both groups of women.Interpretation: In this population-based study of a cohort of women whose use of folic acid supplements while pregnant had been previously documented and who had been pregnant for the first time, we found no evidence that daily consumption of 400 microg of folic acid before and during early pregnancy influenced their risk for miscarriage.